American veteran [videorecording (DVD)] - Ives, Stephen; Tempest, Gene; Carey, Drew; Duckworth, Tammy, 1968-; Studi, Wes; Martinez, J. R. (Jose Rene), 1983- (PBS Distribution, 2022)
Today, America has nearly eighteen million living military veterans, from the Greatest Generation to men and women coming home from recent tours in Afghanistan and Iraq. They join the now-silent ranks of American veterans reaching back to our earliest conflict, the Revolutionary War.